MATHEMATICAL TRAUMA STUDENTS’ JUNIOR HIGH SCHOOL BASED ON GRADE AND GENDER - Ayu Faradillah; Leha Febriani (Jurnal Infinity, 2021)
Mathematical trauma is a mental condition of students caused by experiences that make it difficult or emotionally with mathematics. This study analyzes students’ trauma of mathematics based on grade and gender by using survey research methods and data processing using Winsteps. The subjects of the research were 204 students in every grade in Junior High School. The questionnaire consisted of 20 statements. This instrument was developed measuring mathematical trauma. It consisted of three indicators: difficult to adapt to the environment, saturated with the learning system that is done, and difficult to get along and organize themselves. Based on the Rasch analysis, for the item, two items (I10 and I7) are a misfit, and the rest items are fit. The items were suitable for 147 respondents (72.06%). Based on The Wright Maps table on WinSteps, the percentage of male students who are very traumatized by mathematics is more than female students. Meanwhile, based on grade, students from grade 8 are more very traumatized by mathematics than students from grade 7 and grade 9. Furthermore, based on a questionnaire, students prefer to class condition that made very traumatized by mathematics.